Phytochemical Screening and Anti-microbial Activity Studies on Leea macrophylla Seed Extracts - Islam, M. B.; Sarkar, M. M. H.; Shafique, M. Z.; Jalil, M. A.; Haque, M. Z.; Amin, R. (Journal of Scientific Research, 2013)
Seed extracts of medicinal plants Leea macrophylla were investigated for phytochemical as well as antibacterial screening. Phytochemical studies of the plant extracts revealed the presence of phenolic, saponin, glycosides, carbohydrate and protein types of compounds. The antibacterial effects of the plant extracts were also tested against several human multi-drug resistant pathogens, including one gram positive and three gram negative bacterial species and one fungal species using the disc-diffusion assay. All the plant extracts showed potent anti-microbial effects against gram positive micro-organism (inhibition zone 7-19 mm) whereas none of the extracts produced any potent anti-microbial effects against gram negative bacteria. Furthermore, it has been shown that the extracts exhibit antifungal activities against candida albicans except the extract n-hexane. Keywords: Leea macrophylla; Phytochemical screening; Anti-microbial activity. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i2.13213 J. Sci. Res. 5 (2), 399-405 (2013)